Pemanfaatan Media gambar pada metode langsung Pembelajaran Bahasa Arab di akun Youtube Shirotul mustaqim (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to describe the use of visual image media in the application of the direct method in Arabic language learning through the YouTube channel Shirotul Mustaqim. Arabic language learning often faces difficulties, especially in understanding vocabulary and meaning, particularly for learners who are not accustomed to using the target language directly. Therefore, appropriate methods and media are needed to support effective learning. The direct method emphasizes the use of Arabic actively without translating it into the learners’ mother tongue. This research employed a qualitative approach with a descriptive research design. The data sources were obtained from Arabic learning videos uploaded on the Shirotul Mustaqim YouTube channel. Data were collected through observation and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the use of image media helps learners understand Arabic vocabulary contextually, increases learners’ interest and motivation, and supports the effective implementation of the direct method. Thus, visual image media play an important role in enhancing the effectiveness of digital-based Arabic language learning.